An Exploration of Children Play Learning Space at Seri Iskandar, Perak - Abdullah, Marina; Teh, Mohd Zulhaili; Wan Ali, Wan Noor Anira (International Journal of Sustainable Construction Engineering and Technology, 2023)
Play learning space is beneficial for children's health and education especially at school. Therefore, the study highlighted the character that need to enhance of indoor and outdoor in finding the most preferred play learning space that close to children at school. Moreover, both settings have strengths that can affect children in engaging play learning. A total of 4 themes of elements found in the settings have been highlighted for indoor and outdoor, which consist of a space of playground, plants, water, and animals setting of environments. This study carried on the assessing of preferred tendencies by children (n=128) aged 5 to 6 years old at Seri Iskandar, Perak more likely indoor or outdoor environments for engagement in play learning space. Pictorial studies through photo elicitation and interviews have been carried out at kindergartens around Seri Iskandar, Perak. Analysis using the R-software to obtain a mean comparison will be done to see the tendency of the choice. Future studies can be expanded to see the spatial characteristics that is essential to have in school so that children feel belonging and increase happiness level when they have their play-based learning at school.